Laryngocele masquerading as a soft tissue neck mass - Dhungel, K; Gupta, MK; Ahmad, K; Sah, PL; Rauniyar, RK (Kathmandu University Medical Journal, 2010)
Laryngocele is a rare entity which can clinically present as a neck mass and requires Computed Tomography (CT) and laryngoscopy for diagnosis. We present an interesting case of bilateral laryngocele in a 45 -year-old male presented clinically as hoarseness and left sided neck mass without any history of predisposing factors. Ultrasonography (USG) and CT features of laryngocele is also presented here. Key words: Laryngocele; Cervical mass; Ultrasonography; Computed Tomography DOI: 10.3126/kumj.v7i4.2767 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 423-425